Performance assessment of 14 soil salinity spectral indices in a drought Oasis environment: Rheris Oasis, Southeastern Morocco - Ismail Ait Lahssaine; Lahcen Kabiri; Badre Messaoudi; Mohammed El Hafyani; Badre Essafraoui; Helen Alice Kretzschmar; Edgardo Canas Kurz; Ulrich Hellriegel; Jan Hoinkis (Scientific African, 2025)
Worldwide, soil salinization can also be recognized as a critical indicator of Land Neutrality Degradation (LND). In this study, the Rheris Oasis in southeast Morocco was chosen as a prototype oasis ecosystem to assess the 14 developed soil salinity spectral indices and their performance in the spatiotemporal monitoring of soil salinity during 32 years. And the Standardized Precipitation Anomaly Index (SPAI) was used to understand the drought impact on the soil salinization process. For this purpose, a combined approach of field data (electrical conductivity) and a statistical model were applied. The findings showed that the best Soil Salinity Spectral Index in the study area was reached with a second order polynomial model for salinity index (SI) that reached an adjusted coefficient of determination R2 of 0.914 and a Root-mean-square error of RMSE = 0.997 dS/m. The investigation highlighted a marked reduction in the areas of non-saline soils (electrical conductivity EC < 2 dS/m) within the Rheris oasis, showing a significant decrease by 4.28 km². These areas, previously unaffected by salinity, were notably favorable to agricultural activities. Simultaneously the share of strongly saline soils in the study area almost doubles from 23 % to 40 %. These results can be a basic approach for spatiotemporal soil salinity monitoring in other Oasis contexts and can be used by policy makers to assist local farmers in selecting suitable sustainable agricultural practices.